Feasibility study of public-private partnership - Meidutė, Ieva; Paliulis, Narimantas Kazimieras (International Journal of Strategic Property Management, 2011)
Public-private partnership may cover various forms of partnership, viz. as the property of the private sector in the state of municipal activities or information and consultations between the public and private sectors, also as an unconventional method of public procurement when the public and private sectors enter into a long-term contract on the establishment of public infrastructure or the provision of public services. The most important thing in implementing PPP projects is to properly draw up the contract between the public and private partners, which should explicitly state all terms and conditions, undertakings and liabilities, evaluate risks, determine the payment mechanism and dispute settlement procedure, etc. In order to reduce any risk associated with such projects, a proper legal framework should be developed, which would provide liabilities and undertakings of both parties of the project (the private and public sectors), and more information should be disbursed as to how such projects are being implemented, what the structures of financing are, and what the benefit of such projects is.First Publish Online: 5 Oct 2011